The Implementation Level the strategic thinking and its relation with the level of the organizational ambidexterity. : Of the administrative leaderships at the Directorate of Youths and Sports –wilayat of Msila- - صواش عيسى; دحية خالد (Journal of Sport Science Technology and Physical Activities, 2024)
This study aims at knowing the level of exercising the strategic thinking by the administrative leaderships of the Directorate of Youths and Sports of M’sila from the perspective of the employees. In addition, it aims at knowing the level of their ambidextrous organization and the nature of the relationship between the strategic thinking and the ambidextrous organization of the administrative leaderships of the same Directorate. We used the descriptive relational methodology and used questionnaire that had been distributed to a random sample of 35 employees .Findings show there is a statistically significant relation between the strategic thinking and organizational ambidexterity It is recommended that strategic thinking be developed in a holistic manner.